Avaliação do branqueamento de colônias de Palythoa caribaeorum em regiões com diferentes graus e tipos de impactos antrópicos, na APAMLN (Ubatuba - SP, Brasil) - Bueno, Amanda Escarabichi [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Multiple natural and human stressors can affect the health of hard corals and zoanthids, inducing several adverse effects such as bleaching. The zoanthid Palythoa caribaeorum is an important structurer of the benthic community and occurs on a large scale recovering rocky reefs across the Southeastern Brazil. There is no previous information on the health of zoanthids in the Environmental Protection Area of the North Coast of São Paulo State (APAMLN), despite the importance of these data for decision making. This study aimed to assess the percentage and degree of bleaching on the colonies of P. caribaeorum located in three sites within the APAMLN (Praia do Lázaro, Praia do Flamengo and Ilha das Couves) and relate the data obtained with the potential environmental impacts existing in each sampling site. The coverage of zoanthids was sampled in the summer of 2021, along 25m transects, in which photos were taken considering the area determined by a sample square. Water samples were collected in each site for physicochemical analysis, while human activities potentially capable to affect the colony's health were identified, and the relative environmental pressure index (REPI) was calculated. The polyp's colors were analyzed through the ImageJ program and the Coral Health Chart. In all transects, no mean percentage lower than 23% was found for the intense bleaching degree. Ilha das Couves showed the worst scenario and had the highest value of REPI (27). Only with these data, it was not possible to relate the bleaching of P. caribaeorum with the anthropic impacts. So far, the main information obtained was the bleaching record of P. caribaeorum colonies in Ubatuba, which was not previously recorded.

Múltiplos estressores, naturais e antrópicos podem afetar a saúde dos corais e zoantídeos, causando diversos efeitos, como o branqueamento. O zoantídeo Palythoa caribaeorum é um importante estruturador da comunidade bentônica e ocorre em larga escala nos recifes rochosos da região Sudeste do Brasil. Não há informação sobre a saúde dos zoantídeos na APAMLN, sendo que esses dados são importantes para subsidiar a tomada de decisões. O estudo tem como objetivo fazer uma avaliação da porcentagem e do grau de branqueamento da cobertura de Palythoa caribaeorum em locais dentro da APAMLN e relacionar os dados obtidos com os impactos ambientais existentes nos locais de estudo, sendo eles a Praia do Lázaro, Praia do Flamengo e a Ilha das Couves em Ubatuba-SP. A cobertura dos zoantídeos foi amostrada no verão de 2021, ao longo de transectos de 25m, nos quais fotos foram feitas utilizando um quadrado amostral. Coletas de água foram realizadas em cada praia, para análises físico-químicas. Para cada área, foram identificadas as atividades humanas potencialmente capazes de afetar a saúde das colônias, e a partir disso foi calculado o índice de pressão ambiental relativa (REPI). A coloração dos pólipos foi analisada por meio do programa ImageJ e por meio do Coral Health Chart. Em todos os transectos feitos não foi encontrada nenhuma porcentagem média menor do que 23% para o grau de branqueamento intenso. A Ilha das Couves foi o local com o pior cenário encontrado e com maior valor de REPI (27). Apenas com os dados dessa pesquisa não foi possível fazer uma relação direta do branqueamento de P. caribaeorum com os impactos antrópicos, sendo que a principal informação gerada até momento por esta pesquisa foi o registro de branqueamento das colônias de P. caribaeorum na região de Ubatuba, até então inexistente.
Evaluation of bleaching of Palythoa caribaeorum colonies in regions with different degrees and types of anthropic impacts, at APAMLN (Ubatuba - SP, Brazil).
Keywords: Zoantídeos; Qualidade Ambiental; Branqueamento de corais